Thin-walled ware from Kom al-Ahmer (Alexandria, Egypt) - Mondin, Cristina (Rei Cretariae Romanae Fautorum Acta, 2023)
In the 2019 excavation season, a part of a Roman house was excavated; thirteen well-preserved forms of thin-walled beakers and bowls were found among the material culture. The vessels’ fabric and surface treatments allow their provenance to be hypothesised from numerous production sites. Until today, no thin-walled ware kilns have been attested in the Western Nile Delta; however, the technical characteristics of the fabric and the abundance of clay in this area can suggest the existence of a regional production for two of these forms.